Antibacterial activity of Morinda citrifolia Linneo seeds against Methicillin-Resistant Staphylococcus spp. (March 2019) - De La Cruz-Sánchez, Natividad Giovana; Gómez-Rivera, Abraham; Alvarez-Fitz, Patricia; Ventura-Zapata, Elsa; Pérez-García, Ma Dolores; Avilés-Flores, Margarita; Gutiérrez-Román, Ana Silvia; González-Cortazar, Manasés
Abstract: In traditional medicine, Morinda citrifolia (Noni) is used to treat various ailments, including skin and respiratory-tract infections. In this work, a bio-directed study (seed extracts) with five bacteria was carried out against four clinical isolates of Methicillin-Resistant Staphylococcus (MRS) and Staphylococcus aureus ATCC 29213 strain to find molecules capable of inhibiting them. Three organic extracts were obtained by maceration of the noni seeds with ascending polarity solvents ( n -hexane, dichloromethane and methanol) that were evaluated as antibacterial in the model of bioautography and broth microdilution techniques. The results showed that the methanolic extract was the most active against all bacteria (MIC = 16 mg/mL). The chromatographic fractionation performed on this extract allowed obtaining six fractions (EMF1-EMF6), of which F1, F2 and F5 exhibited activity against some of the bacteria. EMF1 fraction reached an MIC of 25 μg/mL against S. haemolyticus twice as much as the positive control, in which the chemical content is mainly composed of a mixture of γ-butyrolactones (1 –2 ) and esterified fatty acids (3 –9 ); chemical characterization of the nine compounds was carried out based on gas chromatography coupled to masses. EMF2 fraction, presented an MIC of 200 μg/mL against S. aureus 0198 and S. haemolyticus 562B, where a coumarin known as scopoletin (10 ) was isolated and active against S. aureus 0198 (MIC = 100 μg/mL). EMF5 fraction demonstrated an MIC of 200 μg/mL against S. aureus 0198, S. haemolyticus 562B and S. epidermidis 1042, in which a neolignan known as americanin A (11 ) was identified, showing activity against S. haemolyticus 562B and S. epidermidis 1042 (MIC = 100 μg/mL). The chemical characterization of isolated compounds10 and11 was performed by the analysis of 1 H and 13 C NMR. Therefore, the methanolic extract, identified and isolated compounds showed important antibacterial activity against the MRS, validating its use in traditional medicine. Graphical abstract: Image 1 Highlights: The methanolic extract of M. citrifolia seeds showed antibacterial activity resistant to methicillin. The mixture of γ-butyrolactones and fatty acids were active against S. haemolyticus 731B. Americanin A isolated from M. citrifolia was active against S. haemolyticus 562B and S. epidermidis 1042.